IMPROVING READING COMPREHENSION FOR THE FIRST GRADE STUDENTS AT MTs N 1 SURAKARTA BY USING FLASHCARD (A CLASSROOM ACTION RESEARCH) - ENDRAWATI, EVI (2011)
This study aims at describing whether or not the technique of flashcard is able to improve the students' reading comprehension, describe the implementation of teaching reading by using flashcard, classifying the students' responses on implementations of teaching reading by using flashcard and to describing the strength and weaknesses in teaching reading comprehension by using flashcard at MTs N 1 Surakarta. Achieving the object of this research the researcher uses a classroom action research (CAR) each cycle of this research consists of four steps; planning, acting, observing, reflecting. The research was held in MTs N 1 Surakarta with 35 students. In analyzing the data, the researcher uses descriptive analysis. There were two cycle in this research in each cycle is conducted two meetings. After analyzing the data, the result of research shows that the use of flashcard could improve the students' reading comprehension. Through flashcard the students became more active and enthusiast in teaching reading in the classroom. They could comprehend the reading text. In which the students' average pre test is 3, 0, in post test is 7, 0 it indicates that the students have an improvement in reading comprehension. The researcher finds some strength in using flashcard. Flashcard makes them easier to comprehend, and memorize the generic structure of descriptive text. The weaknesses are the finance material aspect, difficulty in managing the class and the different capability of the students.